Commodities futures pricing and approximation of convenience yield for Brent and WTI crude oils - Mlost Karol (My University, 2007)
The purpose of this master thesis is to explain the role of convenience yield on a commodities market and to present recent adaptation of the model for valuation of shares marketability restriction by Heaney to the futures pricing of metals: crop, lead and zinc. The thesis of this work is that for Brent and WTI crude oil, adjusting the classical no arbitrage futures pricing model with approximation of convenience yield by Heaney, gives better results, closer to the observed futures prices, than a simple futures pricing model without adjustment. The master thesis is organized as follows. The first chapter provides basic information about commodities trading and character of this market, explains the difference from a financial market, and provides characteristics of trading assets, conditions and participants. This knowledge is essential to introduce commodities futures pricing theory essence – the convenience yield. The second chapter is the presentation of various approaches to estimate the value of a convenience yield. It shows how these models were evolving during past two decades and briefly describes basic assumptions and main ideas of few models. Being aware of the basic drivers of the commodity market and knowing recent approaches to commodity futures pricing, the third chapter introduces the model of Heaney, a very interesting adaptation of the share marketability valuation model. Principal contribution of this chapter is to explain the origins of the model and to present the final equation for approximation of convenience yield. The fourth chapter describes Brent and WTI crude oils – underlying assets of the test performed in order to examine usefulness of the model of Heaney. When the crude oil related issues are explained, following parts of chapter 4 present analysis of the crude oil data, the method of the test and the description of results for approximation of convenience yield. Results of the test are discussed in chapter 5, along with commodity related issues that might have made an impact on the results, as well as advantages and disadvantages of the model. Finally, all findings of this master thesis are concluded in summary.
Wycena kontraktów futures na rynkach towarowych i oszacowanie convenience yield dla ropy Brent i WTI
Keywords: finance; commodities market; pricing; convenience yield; crude oil; commodity futures prices